Structural, optical and sensing properties of cobalt and indium doped zinc oxide prepared mechano-chemically - Manamela, Mahlatse Fortunate (My University, 2018)
The mechano-chemical technique was employed to synthesise the undoped, cobalt and indium single and double doped ZnO nanoparticles powder samples. The x-ray diffraction (XRD), scanning electron microscopy (SEM), raman spectroscopy (RS), ultraviolet-visible spectroscopy (UV-vis), and photoluminescence (PL) spectroscopy were employed to characterise the prepared samples. The XRD and energy dispersive spectroscopy (EDS) results confirmed that the prepared samples were of hexagonal wurzite form. In addition, it was found that the diffraction pattern for In-ZnO nanoparticles display an additional peak which was associated with In3+ dopant. The peak suggest that In3+ ions prefer the interstitial site in the hexagonal ZnO structure. Doping the ZnO nanoparticles with Co and In did not significantly affect the lattice parameters but the average grain sizes of the nanoparticles were found to be reduced. The morphology of the samples revealed by the SEM images appear to be more spherical. The Raman modes obtained from the excitations wavelength of 514.532 nm further indicated that the prepared samples were of hexagonal ZnO structures. The energy band gap of the prepared samples were calculated from the UV-vis data which showed that the doped ZnO nanoparticles had smaller energy band gap compared to the undoped ZnO nanoparticles. The excitation wavelength of 350 nm were used in the PL study where various defects related emissions were observed for the doped and undoped ZnO nanoparticles. The kenosistec station equipment was used to investigate the prepared samples for gas sensing application. Ammonia (NH3), methane (CH4) and hydrogen sulphide (H2S) gases were probed. In all the response curves observed, the undoped and double doped ZnO nanoparticles are being favoured at a temperature range 200 – 350oC. In addition, the double doped ZnO nanoparticles was found to be more sensitive to CH4 at low temperatures and low v concentrations.
Thesis ((MSc. (Physics)) -- University of Limpopo, 2018
Keywords: Cobalt; Indium; Zink oxide; Zinc oxide; Metal oxide semiconductor